A Phase 1, Dose-escalation, Double-blind, Block-randomized, Controlled Trial of Safety and Efficacy of Neosaxitoxin Alone and in Combination with 0.2% Bupivacaine, with and without Epinephrine, for Cutaneous Anesthesia. (October 2015) - Lobo, Kimberly; Donado, Carolina; Cornelissen, Laura; Kim, Joseph; Ortiz, Rebeca; Peake, Roy W. A.; Kellogg, Mark; Alexander, Mark E.; Zurakowski, David; Kurgansky, Katherine E.; Peyton, James; Bilge, Aykut; et al.
<x xml:space="preserve">Abstract</x> Background: Neosaxitoxin (NeoSTX) is a site-1 sodium channel blocker that produces prolonged local anesthesia in animals and humans. Under a Food and Drug Administration–approved phase 1 Investigational New Drug trial, the authors evaluated safety and efficacy of NeoSTX alone and combined with 0.2% bupivacaine (Bup) with and without epinephrine. Methods: The authors conducted a double-blind, randomized, controlled trial involving healthy male volunteers aged 18 to 35 yr receiving two 10-ml subcutaneous injections. Control sites received Bup. In part 1, active sites received (1) 5 to 40 μg NeoSTX+Saline (NeoSTX-Saline), (2) 5 to 40 μg NeoSTX+Bup (NeoSTX-Bup), or (3) placebo (Saline). In part 2, active sites received 10 or 30 μg NeoSTX+Bup+Epinephrine (NeoSTX-Bup-Epi) or placebo. Primary outcome measures were safety and adverse events associated with NeoSTX. Secondary outcomes included clinical biochemistry, NeoSTX pharmacokinetics, and cutaneous hypoesthesia. Results: A total of 84 subjects were randomized and completed the two-part trial with no serious adverse events or clinically significant physiologic impairments. Perioral numbness and tingling increased with NeoSTX dose for NeoSTX-Saline and NeoSTX-Bup. All symptoms resolved without intervention. NeoSTX-Bup-Epi dramatically reduced symptoms compared with other NeoSTX combinations (tingling: 0 vs. 70%, P = 0.004; numbness: 0 vs. 60%, P = 0.013) at the same dose. Mean peak plasma NeoSTX concentration for NeoSTX-Bup-Epi was reduced at least two-fold compared with NeoSTX-Saline and NeoSTX-Bup (67 ± 14, 134 ± 63, and 164 ± 81 pg/ml, respectively; P = 0.016). NeoSTX-Bup showed prolonged cutaneous block duration compared with Bup, NeoSTX-Saline, or placebo, at all doses. Median time to near-complete recovery for 10 μg NeoSTX-Bup-Epi was almost five-fold longer compared with Bup (50 vs. 10 h, P = 0.007). Conclusion: NeoSTX combinations have a tolerable side effect profile and appear promising for prolonged local anesthesia.